Coalition politics and democratic consolidation in Asia - Sridharan, Eswaran (Oxford University Press, 2012)
This volume compares patterns of coalition politics vis-a-vis the institutionalization of democracy in four Asian developing and multi-ethnic countries. The cases cover India, Sri Lanka Malaysia, and Japan, all of which have experienced a significant period of coalition politics.